The Potential of Vā Part 1: Working in the space between - Simati-Kumar, Benita (Te Kaharoa, 2021)
This article is part of a series of chapters that composed an exegesis, submitted in fulfilment of the requirements for the degree of Doctor of Philosophy. The series is a narrative of discovery through practice-led research. Each article reveals its purpose and significance that leads into the next series, which then eventuate to that final design proposal.The exegesis is presented in this format, to break down the components that assisted in practice-led research. Each article can be read and unpacked on its own as a learning tool. The purpose of this edited series is for the exegesis to be more accessible and adaptable creatively to those being introduced to practice-led research.The Potential of Vā Part 1: Working in the space between, presents the contents and an introduction of the exegesis, it positions the research by placing the present investigation in the context of the writer’s previous work. This chapter outlines the contemporary artistic context in which this thesis exists, it also presents in detail the methods employed in the first phase of the research, and the use of traditional knowledge to form the Lala-Vā model framework.